Needs and problems of physical education teachers in the elementary schools of Cagayan - Callangan, Encarnacion Bancud 1940- (1976)
This study was aimed to survey pertinent information and data regarding the needs and problems of physical education teachers in the elementary schools of Cagayan during the school year 1975-1976. Specifically, it sought to gather data regarding the education, training and experiences of physical education teachers, current practices and problems in the teaching of physical education. To gather factual information for the study, the researcher used questionnaires administered to all physical education teachers. The findings of the study suggest that physical education teachers in the division are not physical education specialists, hence, lack the adequate training to teach the subject. Majority of schools do not have the minimum necessary facilities and equipment needed for the proper implementation of the physical education program.
Vita.
Thesis (M.A.T. Physical Education)--University of the Philippines, Diliman.
Keywords: Physical education teachers -- Philippines -- Tuguegarao (Cagayan).; Elementary teachers -- Philippines -- Tuguegarao (Cagayan).